„MOWA DO MŁODYCH” ŚW. BAZYLEGO WIELKIEGO WSPÓŁCZESNE PRÓBY OCENY, INTERPRETACJE ORAZ INSPIRACJE ZAWARTYCH W N - Szablewska, Elżbieta (Colloquia Litteraria, 2009)
St. Basil’s Address to Young Men. Modern evaluations and interpretations of its pedagogical concepts St Basil’s famous Address to Young Men, on How They Might Derive Benefit from Greek Literature from the time of late antiquity through the Byzantine period up to the modern times has attracted the attention of successive generations of moralists and scholars of different types. While in the Byzantine era and later in Renaissance Europe the treatise was highly estimated for its appreciation for the classical Greek tradition, nowadays the issue of the general meaning of St Basil’s essay is still under discussion. There are still many questions pertinent to this text, e.g. the issue of date and addressees, that can raise doubts among many scholars. Besides, the issue on where to find the source of inspiration for his pedagogical ideas is also a matter of profound importance. The close examination of the treatise done in recent times, first an foremost, by M. Naldini and A. Pastorino reveals that this essay (written probably in the years of his episcopate) can be derived from the spirit of Origen’s paideia.